Remediating Students’ Misconceptions on Fractions through Conceptual Change Theory and Scaffolding - Fikriyah; Maison; Nizlel Huda (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Students’ misconceptions about fraction concepts remain prevalent and significantly impact their mathematical understanding. The purpose of this study was to provide remediation to students who were identified as having misconceptions about fractions based on the results of a diagnostic pre-test using a five-tier instrument. Remediation of students' misconceptions was carried out through learning using conceptual change theory and scaffolding. To determine the impact of the intervention, a post-test diagnostic was conducted using the five-tier instrument. This study employed a mixed-methods approach through a convergent parallel design. The quantitative subjects consisted of 26 students, while the qualitative subjects comprised three students selected through purposive sampling. Qualitative data were collected through observation, interviews, and documentation. The results of this study indicate that before remediation, the average scientific conception (correct answers) was low at 17.6%, and after remediation, it increased to 86.6%, representing an average increase of 69%. The findings indicate that integrating conceptual change theory with scaffolding is a promising strategy for addressing entrenched misconceptions in mathematics education.